Proceedings of the 2nd International Seminar on Business, Economics, Social Science and Technology (ISBEST 2019) 2020
DOI: 10.2991/aebmr.k.200522.035
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Public Value Through Reinforcing Entrepreneurial Orientation and Organization: Preliminary Step Toward Entrepreneurial Universities

Abstract: Higher education institutions as public sectors are considered by some to be unable to provide optimal impact in meeting the needs of industries and businesses. This condition raises demands to operate entrepreneurially, leading to commercialization of research result to encourage the acceleration of innovation. Higher education institutions must be encouraged towards an entrepreneurial state of mind. In order to take a preliminary stage, this paper proposed model using 4 variables are: organization, learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The result of EO-SMEs performance studies seems to be somehow consistent in Asia as Mahmood and Hanafi, (2013), Hosseini, Dadfar, and Brege (2014) in Iran, and Nur et al, (2014) in Indonesia all found that EO has a significant effect on SMEs performance. Also recently, Affendy et al (2015) and AbuBakar et al, (2015), in Malaysia, Zhai et al, (2018) in China, and Gupta (2019) in India and Retnawati and Retnaningsih (2019), Syahdana et al, (2020), Arifin and Dewi (2020), Heng and Afifah (2020), Widokarti and Ginting, (2020) Dionysus and Arifin (2020) and Yasa et al, (2020) in Indonesia and Habib et al, (2021) in Bangladesh confirmed the significant positive relationship between EO and SMEs performance in Asia. So also Sajjad et al, (2020) and Asad et al, (2020) in Pakistan.…”
Section: A Eo and Smes' Performancementioning
confidence: 85%
See 1 more Smart Citation
“…The result of EO-SMEs performance studies seems to be somehow consistent in Asia as Mahmood and Hanafi, (2013), Hosseini, Dadfar, and Brege (2014) in Iran, and Nur et al, (2014) in Indonesia all found that EO has a significant effect on SMEs performance. Also recently, Affendy et al (2015) and AbuBakar et al, (2015), in Malaysia, Zhai et al, (2018) in China, and Gupta (2019) in India and Retnawati and Retnaningsih (2019), Syahdana et al, (2020), Arifin and Dewi (2020), Heng and Afifah (2020), Widokarti and Ginting, (2020) Dionysus and Arifin (2020) and Yasa et al, (2020) in Indonesia and Habib et al, (2021) in Bangladesh confirmed the significant positive relationship between EO and SMEs performance in Asia. So also Sajjad et al, (2020) and Asad et al, (2020) in Pakistan.…”
Section: A Eo and Smes' Performancementioning
confidence: 85%
“…In somehow developed economies, Martínez and Martínez (2016) in Mexico, Real et al, (2012) in Spain, Keskin (2006) in Turkey, and Pett et al, (2019) in the USA all found a significant positive relationship between LO and SMEs performance. Like in Asian countries, Amin (2015) and AbuBakar et al, (2016) in Malaysia, Lestari et al, (2018), Haryanto et al, (2017), Syahdana et al, (2020) and Widokarti and Ginting, (2020) in Indonesia, Hussain et al, (2018) in Iran, Daryani and Karimi (2017) and Sawaeana and Ali (2020) in Kuwait and Kittikunchotiwut (2020) in Thailand all established a significant positive association between LO and SMEs performance. Yet, Sarker and Palit (2015) in Bangladesh and Phorncharoen (2020) in Thailand found an insignificant positive relationship between LO and SMEs' performance.…”
Section: Lo and Smes' Performancementioning
confidence: 89%